Kepemimpinan Dalam Perspektif Berbagai Teori Dan Peranannya Dalam Perumusan Visi Lembaga Pendidikan - Rotim, Rotim; Tasliman, Diana; Udin, Tamsik (Jurnal Ilmiah Wahana Pendidikan, 2025)
In the field of leadership, there are three general approaches: Trait Theory, Charismatic Leadership, and Behavioral Theory. This study explores the differences and similarities of these three approaches to leadership vision formation. The analysis aims to reveal the correlation between leadership approaches and vision formation at Al-Multazam Husnul Khotimah Islamic Education Foundation. This research was conducted using a qualitative method with data collection methods through interviews, observation, and document analysis, with the main focus on understanding leadership according to trait theory, charismatic leadership, leadership according to behavioral theory, and its role in the formulation of organizational vision. In YPI Al-Multazam HK, leadership is organized based on Trait Theory and Charismatic Leadership. At the level of head of unit to division, leaders are assessed based on performance. Behavioral theory is used in determining structural officials. The author's suggestion is to consider natural aptitude and performance results in the appointment of leaders and adopt tests such as STIFIN. According to Trait Theory, leadership is influenced by individual leadership traits. Charismatic Leadership emphasizes the influence and inspiration of the leader. Behavioral Theory emphasizes leadership can be learned and developed. Leader effectiveness depends on leadership style and the formulation of a clear vision.